UV- ozone treated graphene oxide/ PEDOT:PSS bilayer as a novel hole transport layer in highly efficient and stable organic solar cells - Rafique, Saqib; Roslan, Nur Adilah; Abdullah, Shahino Mah; Li, Lijie; Supangat, Azzuliani; Jilani, Asim; Iwamoto, Mitsumasa (Elsevier, 2019)
The utilization of UV-ozone (UVO) treated graphene oxide (GO)/PEDOT:PSS bilayer as hole transport layer (HTL) in solution processed organic solar cells (OSCs) is demonstrated. The HTLs were treated with UVO for 0, 5, 10 and 15 min. The 10 min treated OSC showed the best performance and displayed power conversion efficiency (PCE) of 5.24%, much higher than the untreated OSC device. This enhanced performance is mainly driven by improvements in the short circuit current (∼10.82 mA/cm2) as well as the fill factor (∼57%) that is ascribed to the moderate reduction of GO and increased work function (WF) of PEDOT:PSS after UVO treatment, which improved the contact conditions between the HTL and photoactive layer. Consequently, extraction efficiency of the photogenerated holes is increased, while recombination probability of holes and electrons in the photoactive layer is decreased. Moreover, the UVO-reduction of GO and consequently increased conductivity of reduced-GO (r-GO) has been modeled and proved using the density functional theory (DFT) simulation. Meanwhile, the 15 min UVO-treated OSC device showed severe reduction in the PCE that dropped to 2.11%, possibly due to various factors such as decomposition of chemical bonds, significant increase in the series resistance and pronounced drop in the photovoltaic performance parameters.